- Thread starter James5x5x
- Start date

- Joined
- Nov 24, 2012

- Messages
- 1,828

\(\displaystyle \displaystyle X=\frac{e(f-2)^2}{ef}=\frac{e}{e}\cdot\frac{(f-2)^2}{f}=1\cdot\frac{(f-2)^2}{f}=\frac{(f-2)^2}{f}\)

Now, when you plug in \(\displaystyle 1\) for \(\displaystyle f\), what do you get?

I'd like to help, but what is the equation?Hi,

The answer to the equation below is apparently "1" but I just can't seem to get there. If anyone could show me step by step how you get the correct answer I'd really appreciate that. Thanks.

e(f — 2)²

______

ef

e = -4

f = 1

\(\displaystyle \dfrac{e(f - 2)^2}{ef}\) is an expression, not an equation.

If you are supposed to evaluate the expression \(\displaystyle \dfrac{e(f - 2)^2}{ef}\ given\ e = -\ 4\ and\ f = 1\)

\(\displaystyle \dfrac{e(f - 2)^2}{ef} = \dfrac{(f - 2)^2}{f} = \dfrac{(1 - 2)^2}{1} = \dfrac{(-\ 1)(-\ 1)}{1} = \dfrac{1}{1} = 1.\)